The Financial and economic crisis of 2008-2009 and developing countries - Dullien, Sebastian [et al] (UN New YorkUS, 2010)
Examines how the countries of the South were affected by the global economic and financial crisis and how they responded; what lessons the South could learn and what policy agenda needs to be pushed forward to better support the interests of developing countries, least developed countries as well as emerging-market economies.